Interplay of paternal caregiving and screen use habits on early childhood development and children’s tantrums - Emre Sari; Sıddıka Songül Yalçın (Italian Journal of Pediatrics)
Abstract Background This study aims to examine the association for paternal care and father-child screen use with early childhood development and children’s temper tantrums. Method Study file included questions about paternal characteristics, child care, father-child screen habits, and utilized the UNICEF Early Childhood Development Index (ECDI). Factors influencing ECDI-on-track status and children’s responses when screen use was restricted were investigated with Chi-square test and multiple logistic regression. Results The study included 464 fathers having children aged 3–4 years. The findings showed that 89.7% of the children were on track in three out of the four ECDI subgroups. When screen use was restricted, 55.6% of the children engaged in another activity, while 44.4% reacted by crying. Multiple logistic regression analysis revealed that the father’s education level, the child’s age and gender, the starting age for screen usage, the child’s reaction to screen restriction, and having three or more books were associated with ECDI. Furthermore, the child’s reaction to screen restriction was related to the child’s and father’s screen time, the presence of three or more books, the adequacy of care, and being on track in the literacy-numeracy ECDI subgroup. Conclusion Screen usage habits significantly impact early childhood development and children’s reactions to screen restrictions. These findings underscore the importance of educating fathers about the effects of their own and their child’s media habits, the quality of fatherly caregiving, and the presence of books in fostering positive child development.